Identification of Flavonoid C-Glycosides as Promising Antidiabetics Targeting Protein Tyrosine Phosphatase 1B - Athika Rampadarath; Fatai Oladunni Balogun; Charlene Pillay; Saheed Sabiu (Journal of Diabetes Research)
Protein tyrosine phosphatase 1B (PTP1B), a negative regulator of the insulin signaling pathway, has gained attention as a validated druggable target in the management of type 2 diabetes mellitus (T2DM). The lack of clinically approved PTP1B inhibitors has continued to prompt research in plant-derived therapeutics possibly due to their relatively lesser toxicity profiles. Flavonoid C-glycosides are one of the plant-derived metabolites gaining increased relevance as antidiabetic agents, but their possible mechanism of action remains largely unknown. This study investigates the antidiabetic potential of flavonoid C-glycosides against PTP1B in silico and in vitro. Of the seven flavonoid C-glycosides docked against the enzyme, three compounds (apigenin, vitexin, and orientin) had the best affinity for the enzyme with a binding score of –7.3 kcal/mol each, relative to –7.4 kcal/mol for the reference standard, ursolic acid. A further probe (in terms of stability, flexibility, and compactness) of the complexes over a molecular dynamics time study of 100 ns for the three compounds suggested orientin as the most outstanding inhibitor of PTP1B owing to its overall -34.47 kcal/mol binding energy score compared to ursolic acid (-19.24 kcal/mol). This observation was in accordance with the in vitro evaluation result, where orientin had a half maximal inhibitory concentration (IC50) of 0.18 mg/ml relative to 0.13 mg/ml for the reference standard. The kinetics of inhibition of PTP1B by orientin was mixed-type with Vmax and Km values of 0.004 μM/s and 0.515 μM. Put together, the results suggest orientin as a potential PTP1B inhibitor and could therefore be further explored in the management T2DM as a promising therapeutic agent.